Determination of vibration properties of jatropha (jatropha curcas L.) for mechanical harvesting operations - Mohd Rokli Hizra Ramli
Jatropha curcas L., a multipurpose, drought resistant, perennial oil yielding plant belonging to family of Euphorbiaceae is an important alternative for the production of biodiesel. The seeds contain 40% oil that can be processed to produce a high-quality biodiesel fuel, usable in a standard diesel engines without modifications. Presently Jatropha fruits are harvested by hand for further processing where the end products are biodiesel and glycerine. However, manual harvesting is costly whereby the cost constitutes about 60% to 80% of the total production cost. The present mechanical harvesting machinery that is modified from the berries harvesting machinery is not suitable for Jatropha because the harvester will harvest all the fruits available, including the unripe fruits and cause damage to the trees. The research project is aimed at reducing the high cost during harvesting by finding the vibration frequency and force needed to maximize the amount of matured fruit detach, minimize the amount of unripe fruit also do not damage the tree. This information is crucial in the development of a machine for harvesting Jatropha fruits. A prototype of shaker and beater were developed and three different amplitudes (2.5 cm, 3.5 cm and 5.5 cm distance) with range of certain frequency and force will be measured to identify the most optimal combination to obtain the highest percentage of matured fruit detach. Analysis of variance and compariosn of means by Duncan's Multiple Range Test showed that the frequency and force to detach the ripe and unripe fruits is highly significant different (P<0.01). The minimum frequency to detach the ripe fruits is 160 rpm and the maximum is 229 rpm. Meanwhile for the unripe fruits, yhe minimum frequency is 218 rpm and the maximum is 397 rpm. The lowest force that is required to detach the ripe fruits is 0.964 KgF and the highest force recorded is 1.946 KgF while the lowest force to detach the unripe fruits is 1.290 KgF and the highest is 2.208 KgF. A graph that shows the frequency and force value in accordance with level of maturity of fruits was contributed in this research. Prototype shaker that was developed is found suitable to be used to harvest Jatropha and other crops that have similar characteristics of fruits and tree and ready to be commercialized as a portable harvesting machine due to its efficiency and affordability.